Riches, poverty, and the faithful perspectives on wealth in the Second Temple period and the Apocalypse of John - Mathews, Mark D., 1964- (Cambridge : Cambridge University Press, 2013)
"In the book of Revelation, John appeals to the faithful to avoid the temptations of wealth, which he connects with evil and disobedience within secular society. New Testament scholars have traditionally viewed his somewhat radical stance as a reaction to the social injustices and idolatry of the imperial Roman cults of the day. Mark D. Mathews argues that John's rejection of affluence was instead shaped by ideas in the Jewish literature of the Second Temple period which associated the rich with the wicked and viewed the poor as the righteous. Mathews explores how traditions preserved in the Epistle of Enoch and later Enochic texts played a formative role in shaping John's theological perspective. This book will be of interest to those researching poverty and wealth in early Christian communities and the relationship between the traditions preserved in the Dead Sea Scrolls and New Testament"--
Machine generated contents note: Part I. Introduction: 1. The question of wealth in the Apocalypse; Part II. The Language of Wealth and Poverty in the Second Temple Period: Introduction; 2. Dead Sea Scrolls: non-sectarian Aramaic documents; 3. Dead Sea Scrolls: non-sectarian Hebrew documents; 4. Dead Sea Scrolls: sectarian Hebrew documents; 5. Other Jewish literature; Preliminary conclusions; Part III. Wealth, Poverty, and the Faithful Community in the Apocalypse of John: Introduction; 6. The language of wealth and poverty in the seven messages -- Rev 2-3; 7. The present eschatological age -- Rev 4-6; 8. Buying and selling in Satan's world -- Rev 12-13, 18; 9. Final conclusions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Wealth -- Biblical teaching; Bible. -- Criticism, interpretation, etc; Dead Sea scrolls; Jewish religious literature -- History and criticism; RELIGION / Biblical Studies / New Testament; Electronic books